(untitled) (Palíndromo, 2021)
Abstract: Giuseppe Penone’s production, though majorly linked to the tridimentional domain, is not limited to the realization of sculptures, performances, actions, photographs, drawings and installations. His textual production is equally expressive. His artist’s writings have been gathered and published in 2009 under the title of ’Giuseppe Penone Scritti 1968-2008’, by the Museo d’Arte Moderna di Bologna (MAMbo), represented, then, by Gianfranco Maraniello – organizer and author of the volume’s preface –, in partnership with the Birmingham based Ikon Gallery, directed by Jonathan Watkins. Penone’s writings’ translating rights have been given to the present text’s author, and the translation is currently being reviewed. Penone’s writing, as remarked by the artist himself, is a condition for the whole ensemble of his oeuvre’s existence. We present, here, some of the yet unpublished translations of Giuseppe Penone’s artist’s writings, preceded by a comment, given by this author, concerning the main axis of the artist’s poetic.